2023
DOI: 10.3390/cancers15133409
|View full text |Cite
|
Sign up to set email alerts
|

Research Attitude and Interest among Cancer Survivors with or without Cognitive Impairment

Abstract: Background: We examined the research attitudes and willingness to participate in clinical research among cancer survivors with varying degrees of cognitive function. Methods: This is a secondary analysis of data collected through the University of California Irvine Consent-to-Contact registry. Cancer survivors completed the Cognitive Function Instrument (CFI), the Research Attitudes Questionnaire (RAQ), and willingness to participate (WTP) in certain research procedures. Perceived cognitive impairment (CI) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…RAQ scores have been previously shown to be associated with willingness to participate in research, compliance with study protocols, and study completion. 9 , 10 , 11 , 12 In a previous study, we showed the feasibility of using the RAQ in over 1000 family members for individuals with DS, 13 but we still do not understand how individual items on the RAQ compare to those in the general population. In the present report, we explored differences in RAQ scores between healthcare and research enrollment decision‐makers for individuals with DS and those from a more general population, both of which come from research‐friendly registries in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…RAQ scores have been previously shown to be associated with willingness to participate in research, compliance with study protocols, and study completion. 9 , 10 , 11 , 12 In a previous study, we showed the feasibility of using the RAQ in over 1000 family members for individuals with DS, 13 but we still do not understand how individual items on the RAQ compare to those in the general population. In the present report, we explored differences in RAQ scores between healthcare and research enrollment decision‐makers for individuals with DS and those from a more general population, both of which come from research‐friendly registries in the United States.…”
Section: Introductionmentioning
confidence: 99%